8-oxoguanine and 8-oxodeoxyguanosine Biomarkers of Oxidative DNA Damage: A Review on HPLC-ECD Determination - Chiorcea-Paquim, Ana Maria (2022)
Reactive oxygen species (ROS) are continuously produced in living cells due to metabolic and biochemical reactions and due to exposure to physical, chemical and biological agents. Excessive ROS cause oxidative stress and lead to oxidative DNA damage. Within ROS-mediated DNA lesions, 8-oxoguanine (8-oxoG) and its nucleotide 8-oxo-2'-deoxyguanosine (8-oxodG)-the guanine and deoxyguanosine oxidation products, respectively, are regarded as the most significant biomarkers for oxidative DNA damage. The quantification of 8-oxoG and 8-oxodG in urine, blood, tissue and saliva is essential, being employed to determine the overall effects of oxidative stress and to assess the risk, diagnose, and evaluate the treatment of autoimmune, inflammatory, neurodegenerative and cardiovascular diseases, diabetes, cancer and other age-related diseases. High-performance liquid chromatography with electrochemical detection (HPLC-ECD) is largely employed for 8-oxoG and 8-oxodG determination in biological samples due to its high selectivity and sensitivity, down to the femtomolar range. This review seeks to provide an exhaustive analysis of the most recent reports on the HPLC-ECD determination of 8-oxoG and 8-oxodG in cellular DNA and body fluids, which is relevant for health research.